2016
DOI: 10.1186/s13243-015-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Technical solutions to improve global sustainable management of waste electrical and electronic equipment (WEEE) in the EU and China

Abstract: Remanufacturing is recognized as a major circular economy option to recover and upgrade functions from post-use products. However, the inefficiencies associated with operations, mainly due to the uncertainty and variability of material flows and product conditions, undermine the growth of remanufacturing. With the objective of supporting the design and management of more proficient and robust remanufacturing processes, this paper proposes a generic and reconfigurable simulation model of remanufacturing systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…This is the moment when it is decided if you can repair for the second-hand market or will be considered as WEEE (50). 2-Treatment of WEEE, recycling can be defined as a system in which waste materials are collected, sorted and processed in a way that can be used in the production of different and new products (42). Reuse can occur in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…This is the moment when it is decided if you can repair for the second-hand market or will be considered as WEEE (50). 2-Treatment of WEEE, recycling can be defined as a system in which waste materials are collected, sorted and processed in a way that can be used in the production of different and new products (42). Reuse can occur in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the amount of recycled waste increased significantly. Long et al [39] studied the actual end-of-life (EoL) treatment process, including the remanufacturing, refurbishment, repair, recycling, reuse, and disposal of e-waste, and provided guidance for adjusting EU WEEE management to increase component recycling. e above is premised on system dynamics and research into the influencing factors in recycling efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…As per the European Commission, waste components are considered as the main recourses to diminish the dependence on the import of raw materials [18][19][20]. Consequently the recycled polymeric components from the LCDs can be useful for production of new products, which can replaces the usage of virgin materials.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently the recycled polymeric components from the LCDs can be useful for production of new products, which can replaces the usage of virgin materials. Recycling of end-of-life products are considered as a sequence of procedures, which include collection, segregation and re-processing of materials into useful products which have properties less or similar to its parent materials previously employed in products [19,21]. Peeters et al [22] conducted a case study over various waste treatment strategies over end-of-life flat screens, and they have reached a conclusion that recycling rate can be achieved by improving pre-processing operation such as dismantling, product sorting and clustering.…”
Section: Introductionmentioning
confidence: 99%